Die hellenistischen Reliefbecher aus Lousoi Material aus den Grabungen im Bereich Phournoi 1983-1994 - Rogl, Christine (Österreichisches Archäologisches Institut, 2008)
The ancient city of Lousoi was located to west of the well known Artemis Hemera sanctuary, at the foot of Mount Ilias. In the year 1983 the Austrian Archaeological Institute (ÖAI) in Athens started with systematic excavations in two house-complexes which are situated on terraces within the urban area. In the cadastral maps this location is known as "Phournoi". During the excavations, which continued till 1994, around 350 moldmade fragments with relief decoration from the hellenistic period were found. The moldmade bowls form the largest part of these finds. They were used as drinking vessels during the Greek symposion. Apart from larger bowls and a very small bowl ("miniature") there are also relief-decorated craters, amphoras, jugs, funnels and two bowls of which one has a round stand and the other a high foot. A relief-plate of grey clay from Lousoi has already been published elsewhere. With these finds Lousoi offers a wide variety of moldmade relief-decorated pottery. The various vessels could be composed into complete sets. A few bowls have been preserved almost intact, but the majority of the material is fragmentary in various degrees. For the moment the moldmade bowls are dated tentaively by comparing stamps, decoration-schemes and styles with other specimens, not by contexts, within the second and first half of the first century B.C. There are several imported pieces (around 20%) which considerably differ from the regional and local products. This becomes obvious by comparing and analysing stamps, profiles, dimensions, fabrics and other "individual" peculiarities of the bowls. The local production shows various influences but also strong individual features. The quality of the local production varies from very high to rather mediocre. For the locally produced bowls the term "Brown ware/Lousoi" was chosen. A distinction is made between a series 1 and 2 based on the type of rosette-stamp in the bottom medaillon and the profile. A peculiar feature of ancient Lousoi, which nowadays seems lost in the middle of nowhere, are its commercial relations. There are imports from Argos, a centre for moldmade pottery production on the Peloponnese, from the region around Corinth, Sikyon and from Egio. And there is also evidence for strong connections with more northern regions such as Phokis with parallel examples in Amphissa (compare also the honorary inscriptions on bronze from the propylon in the Artemis sanctuary which were found during the old Austrian excavations in the years 1898 - 1899).